Developing a Gamified Mobile Learning Approach for Evaluating Student’s Agricultural Accounting Education - Ali, Fifitri; Bhayangkara, Abdi; Hidayat, Erzi (Politeknik Negeri Bengkalis, 2024)
This study aims to establish an innovative approach to teaching accounting, with a strong emphasis on astudent-centred methodology. The curriculum is thoughtfully designed using an effective teaching framework, with theprimary goal of helping students better understand accounting principles. It introduces a mobile learning environmentwith a focus on gaming, achieved through the development of an accounting mobile game integrated into a mobilelearning system. The study selected a group of 60 accounting students to participate. The curriculum developmentfollowed a quasi-experimental design, combining quantitative data gathered through questionnaires and qualitative dataobtained through interviews. The results highlight the advantages of game-based mobile learning in improving teachingeffectiveness. Moreover, a regression model indicates that information quality and service quality positively predict theintention to use such a learning approach, and this intention, along with user satisfaction, positively influencesengagement in the learning process. Notably, user satisfaction serves as a mediating factor within this relationship. Inconclusion, this study offers valuable recommendations for educators and researchers in the field of accounting, sheddinglight on the benefits of incorporating game-based mobile learning into accounting education.